Reference citations based on digital sources in university theses in the field of education - Abdel Salam, Wafa Mohamed; Khattab, Al-Saeid Mabrouk Ibrahim (Arab Journal for Sciences and Research Publishing, 2016)
This study aims to measure the extent of the use of graduate students in the field of education to electronic sources of information, through reference citations contained in the analysis (277) Thesis have been approved in the field of education at Kafrelsheikh University in the period (2013-2015(. The study results indicated that the theses cited electronic resources accounted for (74%) while the martyrdom electronic resources ratio in these letters (6%), and the messages that have been approved a year (2015) included a higher proportion of the martyrdom of electronic resources, and most sources It cited was in English, and that the majority of these sources belong to two categories (search - electronic article).